Tetra-O-methyl-nordihydroguaiaretic acid inhibits energy metabolism and synergistically induces anticancer effects with temozolomide on LN229 glioblastoma tumors implanted in mice while preventing obesity in normal mice that consume high-fat diets. - Kotohiko Kimura; Jong Ho Chun; Yu-Ling Lin; Yu-Chuan Liang; Tiffany L B Jackson; Ru Chih C Huang (PLoS ONE, 2023)
Tetra-O-methyl-nordihydroguaiaretic acid (terameprocol; M4N), a global transcription inhibitor, in combination with a second anticancer drug induces strong tumoricidal activity and has the ability to suppress energy metabolism in cultured cancer cells. In this study, we showed that after continuous oral consumption of high-fat (HF) diets containing M4N, the M4N concentration in most of the organs in mice reached ~1 μM (the M4N concentration in intestines and fat pads was as high as 20-40 μM) and treatment with the combination of M4N with temozolomide (TMZ) suppressed glycolysis and the tricarboxylic acid cycle in LN229 human glioblastoma implanted in xenograft mice. Combination treatment of M4N with TMZ also reduced the levels of lactate dehydrogenase A (LDHA), a key enzyme for glycolysis; lactate, a product of LDHA-mediated enzymatic activity; nicotinamide phosphoribosyltransferase, a rate-limiting enzyme for nicotinamide adenine dinucleotide plus hydrogen (NADH)/NAD+ salvage pathway; and NAD+, a redox electron carrier essential for energy metabolism. It was also shown that M4N suppressed oxygen consumption in cultured LN229 cells, indicating that M4N inhibited oxidative phosphorylation. Treatment with M4N and TMZ also decreased the level of hypoxia-inducible factor 1A, a major regulator of LDHA, under hypoxic conditions. The ability of M4N to suppress energy metabolism resulted in induction of the stress-related proteins activating transcription factor 4 and cation transport regulator-like protein 1, and an increase in reactive oxygen species production. In addition, the combination treatment of M4N with TMZ reduced the levels of oncometabolites such as 2-hydroxyglutarate as well as the aforementioned lactate. M4N also induced methylidenesuccinic acid (itaconate), a macrophage-specific metabolite with anti-inflammatory activity, in tumor microenvironments. Meanwhile, the ability of M4N to suppress energy metabolism prevented obesity in mice consuming HF diets, indicating that M4N has beneficial effects on normal tissues. The dual ability of combination treatment with M4N to suppress both energy metabolism and oncometabolites shows that it is potentially an effective therapy for cancer.